For God Has also Lost a Son. A Biblical Perspective on Exile - Alonso Vicente, Pablo José (Jesuit Refugee Service (Roma, Italia), 2005)
.

This chapter offers a biblical and theological reflection on exile, forced displacement, and refugee experience. Drawing on the Old Testament, especially the experiences of Israel in Assyrian and Babylonian exile, it argues that exile is never to be idealized, since it is rooted in violence, injustice, and suffering. Yet the biblical tradition also presents exile as a place where God remains close, accompanies the suffering, and invites people into deeper conversion, hope, and solidarity. The chapter connects this perspective with the life of Jesus, especially the flight into Egypt and his identification with the stranger, the hungry, and the vulnerable. It also reflects on Jesus’ encounter with the Syrophoenician woman as a model for crossing cultural, religious, and social boundaries. Ultimately, the text presents exile not only as a wound but also as a possible cornerstone for renewed faith, compassion, and mission among refugee
Capítulos en libros